the Effect of E-Service Quality and Customer Satisfaction on Repurchase Intention Through Online Consumer Review as Intervening Variables in the Marketplace Shopee - Mahyunnisa yunus; Amrin Fauzi; Endang Sulistya Rini (Journal Research of Social Science, Economics, and Management, 2022)
The purpose of this study was to determine the effect of e-service quality and customer satisfaction on repurchase intention through online consumer reviews tool as an intervening variable on the marketplace Shopee. The population in this study were women aged 20-35 years and had purchased and used the marketplace Shopee at least 2 times in Medan City with a total sample of 190 respondents. The sampling technique in this study was the sample taken with a non-probability sampling design. The type of non-probability sampling used was accidental sampling. The results show that E-service quality has a positive and significant effect on online consumer reviews on the marketplace Shopee. Customer satisfaction has a positive and significant effect on online consumer reviews on the marketplace Shopee. E-service quality has a positive and insignificant effect on repurchase intention in the marketplace Shopee. Customer satisfaction has a positive and significant effect on repurchase intention in the marketplace Shopee. Online consumer reviews have a positive and significant effect on repurchase intention in the marketplace Shopee. E-service quality has a positive and significant effect on repurchase intention through online consumer reviews as an intervening variable in the marketplace Shopee. Customer satisfaction has a positive and insignificant effect on repurchase intention through online consumer reviews as an intervening variable in the marketplace Shopee.